Effect of Limestone Particle Size and Potassium Supplementation on Growth Performance, Blood Physiology, and Breast Muscle Myopathy of Male Broiler Chickens - Joardar, Dinabandhu; Livingston, Kimberly A.; Edens, Frank W.; Nusairat, Basheer; Qudsieh, Rasha; Livingston, Matthew L.; Brake, John (Frontiers in Veterinary Science, 2020)
The experiment investigated the effects of limestone particle size and dietary potassium (K) on live performance, blood physiology, and muscle myopathies in broilers raised to 35 d of age. A total of 384 Ross male broilers were placed in 24 floor pens and fed four diets during the starter (0-16 d of age) and grower (17-33 d of age) periods containing two limestone particle sizes (fine: 0.2 mm and coarse: 0.9 mm), and amended with either 0% basal K (K-) or 0.2% added dietary K (K+) as potassium carbonate to complete the 2x2 factorial arrangement. Live performance was measured from 1-33 d of age. Blood physiology, woody breast (WB) and white striping (WS) scores were measured at 35 d of age. The K+ dietary treatment reduced (P < 0.05) feed intake and BWG when compared to K- during the starter and grower period. The K+ dietary treatment decreased blood Na (mmol/L), blood glucose (mg/dL), ionized blood Ca (mg/dL), TCO2 (mmol/L), blood HCO3 (mmol/L), and base excess in extracellular fluid (mmol/L) when compared to K- birds of similar body weight at 35 d of age (P≤0.05). Fine limestone diets tended to reduce WB scores (3.0 vs. 2.59) when compared to coarse limestone diets at 35 d of age (P=0.08). This study demonstrated that using 0.2% of K as potassium carbonate did not negatively affect FCR even though FI and BWG were reduced. Furthermore, fine limestone has the potential to reduce WB in breast muscle tissues; however, further research is needed to confirm these outcomes.